Dorso-ventral osteophytes of interphalangeal joints correlate with cartilage damage and synovial inflammation in hand osteoarthritis: a histological/radiographical study - Ilse-Gerlinde Sunk; Love Amoyo-Minar; Birgit Niederreiter; Afschin Soleiman; Franz Kainberger; Josef S. Smolen; Daniel Aletaha; Klaus Bobacz (Arthritis Research & Therapy, 2022)
Abstract Objective To detect dorsally located osteophytes (OP) on lateral x-ray views and to correlate their presence with the extent of structural joint damage, determined by histologic grading (cartilage damage and synovial inflammation) and radiographic scoring in hand osteoarthritis (HOA). Methods Distal interphalangeal (DIP) and proximal interphalangeal (PIP) joints were obtained from post mortem specimens (n = 40). Multiplanar plain x-rays were taken (dorso/palmar (dp) and lateral views). Radiographic OA was determined by the Kellgren and Lawrence classification. Joint samples were prepared for histological analysis and cartilage damage was graded according to the Mankin scoring system. Inflammatory changes of the synovial membrane were scored using the general synovitis score (GSS). Spearman’s correlation was applied to examine the relationship between histological and radiographical changes. Differences between groups were determined by Mann-Whitney test. Results Bony proliferations that were only detectable on lateral views but reminiscent of OPs on dp images were termed dorso-ventral osteophytes (dvOPs). All joints displaying dvOPs were classified as OA and the presence of dvOPs in DIP and PIP joints correlated with the extent of histological and radiographic joint damage, as well as with patient age. Joint damage in osteoarthritic DIP and PIP joints without any dvOPs was less severe compared to joints with dvOPs. Synovial inflammation was mainly present in joints displaying dvOPs and correlated with joint damage. Conclusion dvOPs are associated with increasing structural alterations in DIP and PIP joints and can be seen as markers of advanced joint damage. Detecting dvOPs can facilitate the diagnosis process and improve damage estimation in HOA.